Structure of a Mixed Ombrophilous Forest remains in Urupema, Santa Catarina, Brazil - Martins, Daiane; Rodrigues, Aurélio Lourenço; Chaves, Camila Lucas; Mantovani, Adelar; Bortoluzzi, Roseli Lopes da Costa (Revista de Ciências Agroveterinárias, 2012)
The aim of the present study was to describe the structure and floristic composition of the arboreal stratum upper Montane Mixed Ombrophilous Forest, at an altitude of approximately 1650 m, in the Urupema, state of Santa Catarina. Five transections were randomly allocated and subdivided into 146 plots of 10x4m, totaling 5 840 m2. All plants with DBH greater than or equal to 5 cm were included into phytosociological study. Results showed the presence of 1656 individuals per hectare, distributed into 24 families, 32 genera and 42 species. The families with the highest number of species were Myrtaceae (ten), Asteraceae and Lauraceae (three). The horizontal structure of the forest was characterised by the high relative importance of three species: Dicksonia sellowiana Hook., Myrceugenia euosma (O. Berg) Legr. and Drimys angustifolia Miers, with together represented 54.4% of the relative density of the forest, 60.66% of the relative dominance, 40.5% of the relative frequency, and 51.06% of the importance value index. The values of the Shannon diversity index and the Pielou evenness index were respectively 2.6 nats/ind and 0.88. A low diversity was observed in the area, which could be related to the historical land use and to specific environmental conditions due to its high altitude.